Design a model of Image Restoration using AI in Digital Image Processing - Archana S Nadhan, Dioline Sara, Boosi Shyamala, Dr. Chetana Tukkoji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Image restoration is the process of obtaining a distorted/noise image and giving an approximate clear image of the original image. False focus, motion blur and noise are forms of distortion. Image restoration can be done by reversing the process called Point Extension Function (PSF). In this process, the blurred image is generated by point source imaging and can be used to restore the image lost due to the blur process. Like to form. Modern artificial intelligence (AI) applied to image processing includes facial recognition, object recognition and detection, video, image action, and visual search. It helps to develop smart applications in digital image processing.